Enhanced energy extraction in small-scale wind turbines through slot-based passive blowing - Md. Zishan Akhter; Ahmed Riyadh Ali; Hasan Kamliya Jawahar; Farag Khalifa Omar; Emad Elnajjar (Energy Conversion and Management: X, 2023)
The increasing demand for sustainable energy has spurred research and development of wind turbines. In this study, a passive flow-control technique using a non-uniform curved slot is proposed. The slot is engraved on the mid-chord region of the National Renewable Energy Laboratory (NREL) Phase VI wind turbine blade, between the quarter-span and tip radial stations. The impact of slot-induced flow control is investigated using three-dimensional transient computational fluid dynamics (CFD) modeling across a range of wind speeds, including pre-stall and deep-stall conditions. Aerodynamic analyses are performed to ascertain the influence of slot-flow on the complex three-dimensional flow dynamics around the blade. The slotted blade demonstrates significant improvements in low-speed shaft torque and power compared to the baseline blade. Additionally, the slotted blade experiences increment in the inherent thrust and flapwise bending moments. Detailed wake flow field and surface flow visualization indicate that the slot promotes a more streamlined attached flow across the blade span, delaying flow transition and suppressing turbulence on the blade surface and downstream wake. The slot-flow also reduces radial flow and tip-vorticity anomalies along the blade. Overall, flow control enhancement achieved by the slotted blade significantly boosts the annual energy production of the wind turbine.